The Role of Teachers in Improving Student Learning Achievement at SDN 2 Gondang in the 2024/2025 School Year - Putrawadi, Putrawadi; Mahendra, Juandra Prisma; Marzoan, Lalu (Peneliti.net, 2025)
This study aims to describe and analyze the role of teachers in improving student achievement at SDN 2 Gondang in the 2024/2025 academic year. The research method used is a descriptive qualitative approach, with data collection techniques through observation, interviews, documentation, The research subjects consisted of teachers and students of SDN 2 Gondang. The results showed that teachers have a very important role in encouraging increased student learning achievement, both as educators, facilitators, motivators, mentors, and evaluators. Teachers at SDN 2 Gondang use a variety of active and varied learning methods, such as lectures, group discussions, contextual approaches (CTL), as well as the use of learning media in the form of pictures and teaching aids. In addition, teachers also take an individual approach to students who have learning difficulties, and establish communication with parents through liaison books and digital media. Students' learning achievements improve along with the use of appropriate learning methods and strategies as well as emotional and academic support from teachers. This finding confirms that the role of teachers is crucial in creating a conducive learning environment and encouraging students to achieve optimal learning outcomes.